Implementation of Individual Company Policies in Indonesia in the Job Creation Law - Utami, Ismi Maulidya; Mayasari, Ima (Jurnal Indonesia Sosial Sains, 2025)
Ease of doing business is an important indicator for Indonesia's economic growth, especially for the Micro, Small, and Medium Enterprises (MSMEs) sector, which accounts for the majority of GDP and national labor absorption. The implementation of the Individual Company policy through the Job Creation Law is one of the efforts to strengthen this sector. This study aims to evaluate the implementation of Individual Company policies in Indonesia, focusing on the role of the Ministry of Law and Human Rights as a data manager and its impact on the ease of doing business. The method used is a descriptive qualitative approach based on the post-positivism paradigm. Data were obtained through in-depth interviews with relevant actors and analysis of policy documents. The results of the study show that this policy has encouraged an increase in the registration of Individual Companies, reaching 151,355 entities by 2024. However, the main challenges include low adoption of digitalization, limited financial reporting capabilities, and constraints on policy socialization. This policy is considered effective in providing legal protection through the separation of personal and corporate assets, but requires strengthening the socialization and mentoring strategy of MSMEs on an ongoing basis.